Application of contrast-enhanced ultrasonography in evaluating acute testicular lesions: a retrospective analysis - Bin Zou; Yuling Yang; Lusheng Zhang; Huabin Chen; Fuqiang Zeng; Biwei Chen (International Journal of Emergency Medicine)
Abstract Background Acute complete testicular torsion, acute incomplete testicular torsion, acute testicular ischemia, acute testicular appendage torsion, and acute epididymo-orchitis are common scrotal emergencies in urology. An accurate diagnosis of the cause of acute scrotal pain is crucial for selecting the appropriate treatment. This study aimed to explore the application of high-frequency ultrasonography (HFUS) and contrast-enhanced ultrasonography (CEUS) in the evaluation of acute scrotal lesions. Results This study included 46 patients with acute scrotal pain. All patients underwent HFUS and CEUS prior to treatment. The ultrasonographic features of the affected and contralateral (healthy) testes were compared to evaluate the application of HFUS and CEUS for the assessment of acute scrotal lesions. Two patients with testicular ischemia were correctly diagnosed using both HFUS and CEUS. Among the nine patients with complete testicular torsion, eight were correctly diagnosed using HFUS, while one was only diagnosed as having an abnormal testis. In the cohort of 11 patients with incomplete testicular torsion, eight were accurately identified using HFUS, whereas three were erroneously diagnosed as having complete testicular torsion. Among the 15 patients with testicular appendage torsion, 14 were correctly diagnosed using HFUS, while one was misdiagnosed as having testicular torsion. Among the nine patients with epididymitis, seven were correctly diagnosed using HFUS, one was misdiagnosed as having testicular appendage torsion, and one was misdiagnosed as normal. However, CEUS results were consistent with the final confirmed diagnoses. The diagnostic accuracy of HFUS for acute scrotal lesions was 84.8%, whereas that of CEUS was 100%. The discrepancy between the two methods was statistically significant (χ2 = 3.50; P = 0.018, P < 0.05, respectively). Conclusion CEUS has higher accuracy in evaluating acute scrotal lesions. This can prevent misjudgment of the degree of testicular torsion, prevent misdiagnosis of testicular appendage torsion and epididymitis as testicular torsion, and avoid misjudgment of abnormal testes or epididymitides as normal. This helps prevent adverse outcomes such as delayed treatment and testicular removal.